2013
DOI: 10.1128/aem.03965-12
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Transferable Bimolecular Fluorescence Complementation System for the Investigation of Interactions between Poly(3-Hydroxybutyrate) Granule-Associated Proteins in Gram-Negative Bacteria

Abstract: Poly(3-hydroxybutyrate) (PHB) granules are organelle-like multienzyme-polymer complexes (carbonosomes) and are widespread storage compounds in prokaryotes. The interaction of three PHB granule-bound proteins (PHB synthase PhaC1, phasin PhaP5, and PHB/DNA binding protein PhaM) was studied in vivo by bimolecular fluorescence complementation (BiFC) microscopy in Ralstonia eutropha. To this end, a mobilizable 2-plasmid system for arabinose-controlled expression of protein fusions with the N-terminal (YN) and C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The resolution of the gel did not allow a precise determination of the apparent molecular mass. This result was in agreement with previous analysis that suggested the PhaM is present in oligomeric form, most likely as a dodecamer (43). Remarkably, also PhaC1 formed high-molecular-mass complexes of Ն300 kDa.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The resolution of the gel did not allow a precise determination of the apparent molecular mass. This result was in agreement with previous analysis that suggested the PhaM is present in oligomeric form, most likely as a dodecamer (43). Remarkably, also PhaC1 formed high-molecular-mass complexes of Ն300 kDa.…”
Section: Resultssupporting
confidence: 82%
“…Nucleoid occlusion of PHB granules (50) in growing cells might be one explanation for the frequent observation of periphery-localized PHB granules, and this assumption would allow to keep the micelle model. However, the identification of PhaM as a novel PHB-and DNA-bound protein (27,29) and the in vivo interaction of PhaC1 and PhaM in R. eutropha (43) is in disagreement with the assumption of a random localization of PhaC1 in the cytoplasm. It is more compatible with a third model, the scaffold model, in which the PHB synthase PhaC1 is attached to an internal cellular structure, most likely to the bacterial nucleoid.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, Neumann et al proposed that PhaP Re occurs as a trimer (17), and some phasins have been reported to form other kinds of oligomers, such as dimers and dodecamers (corresponding to PhaP5 and PhaM from R. eutropha, respectively) (22). A common structural characteristic of phasins is the presence of coiled-coil interacting regions.…”
Section: Structural Aspects Of Phasinsmentioning
confidence: 99%